2021
DOI: 10.1364/oe.439537
|View full text |Cite
|
Sign up to set email alerts
|

Smoothed accumulated spectra based wDSWF method for real-time wind vector estimation of pulsed coherent Doppler lidar

Abstract: Wind vector estimation method with high accuracy in the low signal-to-noise ratio region improves the performance of pulsed coherent Doppler lidar. The key to improving accuracy is to process the incorrect radial wind estimates or the distorted power spectra better. The smoothed accumulated spectra based weighted sine wave fitting method proposed here minimizes the effects of bad radial wind estimates by considering both signal intensity and wind spatial continuity. Leveraging spatial continuity from smoothed … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 32 publications
1
6
0
Order By: Relevance
“…Previous studies believe that the accuracy of the dynamic programming algorithm is high, but the influence of amplitude variation of accuracy is ignored. This shows that the main reason for the poor accuracy of the dynamic programming algorithm is not the low accuracy, but the large range of accuracy change, which is basically consistent with the relevant domestic research conclusions [ 10 ].…”
Section: Case Studies On Resource Allocation and Management Of Actual...supporting
confidence: 84%
See 1 more Smart Citation
“…Previous studies believe that the accuracy of the dynamic programming algorithm is high, but the influence of amplitude variation of accuracy is ignored. This shows that the main reason for the poor accuracy of the dynamic programming algorithm is not the low accuracy, but the large range of accuracy change, which is basically consistent with the relevant domestic research conclusions [ 10 ].…”
Section: Case Studies On Resource Allocation and Management Of Actual...supporting
confidence: 84%
“…Some scholars also integrated Fourier series and discrete function into allocation and management [ 9 ] and found that classifying public sport facility resources can improve the accuracy of allocation and management and shorten the processing time of public sport facility resources. In short, domestic scholars have integrated the spatial spectrum estimation method, Fourier series [ 10 ], spatial spectrum estimation method, and other comprehensive analysis methods into the analysis process [ 11 ], which can reduce the data dispersion and improve the accuracy of resource allocation and management results of public sport facilities [ 12 ]. Therefore, using the spatial spectrum estimation method to manage public sport facilities resources can not only realize the comprehensive allocation of resources but also improve the management level and realize multifactor analysis.…”
Section: Introductionmentioning
confidence: 99%
“…This process whitens the base noise and helps the correct signal peak to be detected. Subsequently, the spectra were smoothed according to the method proposed by Lin et al for estimating radial wind from smoothed accumulated spectra [39]. Examples of intermediate results are shown in Figure 9.…”
Section: Data Pre-processingmentioning
confidence: 99%
“…With a resolution of only a few tens of meters, the wind measurement lidar is smaller than most wind shear [26]. Based on the spatial continuity of wind speeds in a smooth atmosphere, it is unlikely that wind speeds at adjacent distance doors will change significantly [19]. Thus, according to this characteristic of the wind field, 2D low-pass Gaussian filtering is used to enhance the correlation between the range gates, and then the peak extraction is carried out, which effectively reduces the influence of the peak extraction by the noise and improves the accuracy of the extracted peaks.…”
Section: D Gaussian Filtermentioning
confidence: 99%
“…However, the more commonly used the algorithm, the more free parameters are required. In addition, how to accurately retrieve peaks in low-SNR regions by ignoring the effect of noise is also a challenge for many currently available peak-detection algorithms [19]. Therefore, new spectral signal processing methods are needed to improve data availability.…”
Section: Introductionmentioning
confidence: 99%